Factor analysis of the Zaporizhzhia wind park impact on bats based on the index of their activity and dynamics of species diversity - Gorlov, P.I.; Siokhin, V.D.; Polishchuk, I.K; Volokh, Anatoliі; Gorlova, A.P. (IOP Publishing Ltd, 2022)
EN Based on the studies in the period of 2010-2021, there was obtained some information on the behavior of bats and their species composition at the Zaporizhia wind park in the Zaporizhia Region, Ukraine. In the study area, there was established the presence of 10 species of bats belonging to 7 genera. The most complete results were obtained in 2019, when 4 field research methods were used, 28 expedition trips were carried out and 4177 bat signals were recorded. In total, the information on 43938 bat signals was collected in 2010-2021. The total operating time of the ultrasonic detectors was 4565 hours. There were calculated indices of the voice activity of bats for three research methods by seasons, different functional zones and phases of the annual cycle of animals. Surveys on transects with the geo-position of each recorded signal made it possible to characterize the distribution of bats over the territory of the wind farm, and the use of the Kernel Density tool allowed to differentiate the wind farm site of the Zaporizhia wind park into the zones that are conditionally safe for bats and high-risk zones. There have been determined the periods of the year and time periods of night activity, in which it is advisable to use measures to minimize the negative impact. Using international and own experience, there have been proposed methods for repelling bats away from the wind turbines.
Факторний аналіз впливу Запорізького ВЕС на кажанів за індексом їх активності та динамікою видового різноманіття.
A. M. Volokh https://orcid.org/0000-0003-1291-921X